CHARACTER EDUCATION IN HISTORY LESSON - Nunuk Suryani, Nur Ahyani, Soetarno Joyoatmojo, Muhammad Ahyar & (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2017)
Character refers to a set of knowledge, attitudes, motivations, behaviors and skills. Charactereducation learners can be developed through history. The development of character values areintegrated in every subject of history courses. The values are listed in the syllabus and lessonplan. In forming the characters of the students are integrated in the subjects of history, itsimplementation is supported basic competencies in the curriculum in 2013 organized into fourcore competencies. The first core competencies related to the attitude of self to God Almighty.The second core competencies related to the character of self and social attitudes.Keywords: Character Education, Teaching History